2017
DOI: 10.1182/blood-2017-01-764274
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic and functional integrity of the hematopoietic system requires tolerance of oxidative DNA lesions

Abstract: Key Points Tolerance of oxidative DNA lesions ensures the genomic and functional integrity of hematopoietic stem and precursor cells. Endogenous DNA damage–induced replication stress is associated with mitochondrial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 60 publications
(70 reference statements)
1
25
0
Order By: Relevance
“…While most DNA damages are detected and result in cell cycle arrest or apoptosis, some lesions are bypassed via DNA translesion synthesis that appoints specialized DNA polymerases, wherein Rev1 acts as a core factor. Deletion of Rev1 in hematopoietic system led to loss of engraftment potential of HSCs with functional loss starting as early as in the E14 fetal liver . These results clearly emphasize the importance of DDR pathways and predict the effects of DNA damage accumulations.…”
Section: Balance Between Oxidative and Non‐oxidative Pathways Is The Keymentioning
confidence: 64%
“…While most DNA damages are detected and result in cell cycle arrest or apoptosis, some lesions are bypassed via DNA translesion synthesis that appoints specialized DNA polymerases, wherein Rev1 acts as a core factor. Deletion of Rev1 in hematopoietic system led to loss of engraftment potential of HSCs with functional loss starting as early as in the E14 fetal liver . These results clearly emphasize the importance of DDR pathways and predict the effects of DNA damage accumulations.…”
Section: Balance Between Oxidative and Non‐oxidative Pathways Is The Keymentioning
confidence: 64%
“…It has been reported that the expression of Rev1 is upregulated under replication stress (40). In mammalian cells, deletion of REV1 leads to exacerbation of oxidative stress, cell senescence, and apoptosis (41). Furthermore, elevated expression of Rev1 confers enhanced UV damage tolerance (42).…”
Section: Discussionmentioning
confidence: 99%
“…However, the action of a translesion synthesis DNA polymerase such as REV1, a deoxycytidyl transferase, inserts a cytosine opposite to a uracil, resulting in a C>G transversion 43,44 . Because folate deficiency increases the level of uracil in DNA 45,46 , we propose that it is through the repair of the misincorporated uracil by REV1, present in bone marrow stem cells 47 , that leads to C>G transversions in bone marrow.…”
Section: Discussionmentioning
confidence: 99%